Masseter muscle myofibrillar protein synthesis and degradation in an experimental critical illness myopathy model. - Hazem Akkad; Rebeca Corpeno; Lars Larsson (PLoS ONE)
Critical illness myopathy (CIM) is a debilitating common consequence of modern intensive care, characterized by severe muscle wasting, weakness and a decreased myosin/actin (M/A) ratio. Limb/trunk muscles are primarily affected by this myopathy while cranial nerve innervated muscles are spared or less affected, but the mechanisms underlying these muscle-specific differences remain unknown. In this time-resolved study, the cranial nerve innervated masseter muscle was studied in a unique experimental rat intensive care unit (ICU) model, where animals were exposed to sedation, neuromuscular blockade (NMB), mechanical ventilation, and immobilization for durations varying between 6 h and 14d. Gel electrophoresis, immunoblotting, RT-PCR and morphological staining techniques were used to analyze M/A ratios, myofiber size, synthesis and degradation of myofibrillar proteins, and levels of heat shock proteins (HSPs). Results obtained in the masseter muscle were compared with previous observations in experimental and clinical studies of limb muscles. Significant muscle-specific differences were observed, i.e., in the masseter, the decline in M/A ratio and muscle fiber size was small and delayed. Furthermore, transcriptional regulation of myosin and actin synthesis was maintained, and Akt phosphorylation was only briefly reduced. In studied degradation pathways, only mRNA, but not protein levels of MuRF1, atrogin-1 and the autophagy marker LC3b were activated by the ICU condition. The matrix metalloproteinase MMP-2 was inhibited and protective HSPs were up-regulated early. These results confirm that the cranial nerve innervated masticatory muscles is less affected by the ICU-stress response than limb muscles, in accordance with clinical observation in ICU patients with CIM, supporting the model' credibility as a valid CIM model.